Identification of Dominant Shark Fins Landed at The Port of Benoa, Bali Based on CO1 Gene - Yuni Debora Prasicilia Sitorus; Pande Gde Sasmita Julyantoro; Ayu Putu Wiweka Krisna Dewi (Journal of Marine and Aquatic Sciences, 2022)
Indonesia is one of the world's most shark-catching countries. One of the fishery ports that has a by-product of sharks is the Port of Benoa. The purpose of this study was to determine the species and phylogenetic relationship of sharks from dominant fin samples landed at the Port of Benoa, Bali based on the results of morphological identification and DNA barcoding techniques. The study was conducted from January to February 2018 at the Pengawasan Sumberdaya Kelautan dan Perikanan Base (PSDKP) Benoa. This research uses exploration method with survey technique. The data used in this research is primary data of dominant shark fin samples in research location area and secondary data of location where shark caught by fisherman based on PSDKP database. The results showed that by-catch sharks from dominant fin samples at the Port of Benoa, Bali based on morphological identification and DNA barcoding technique were Prionace glauca (Blue Shark) species. The results of phylogenetic analysis of by-catch shark species from dominant fin samples landed at the Port of Benoa, Bali have close relation with Carcharhinidae family. Prionace glauca shark species have an amplified nucleotide base length of 600 pb with similarity reaching 99 values with species present in GenBank.